Corporate Governance Dynamics and Sustainability Phases in Indonesian Palm Oil: A Multi-Principal Agency Perspective - Maria Dian Nurani; Retno Kusumastuti Hardjono; Mia Siscawati; Renny Nurhasana (Jurnal Manajemen dan Agribisnis, 2025)
Background: Indonesia’s palm oil industry boosts the economy and supports renewable energy, but its expansion has caused deforestation, biodiversity loss, and social conflict. Rising external pressure makes sustainability essential, yet practices remain fragmented. Stronger corporate governance is needed to balance profit with social and environmental responsibility, as traditional agency theory no longer fully applies.Purpose: This study explores how different principal groups influence sustainability phase progression and how governance mechanisms evolve when companies face competing sustainability expectations in the agribusiness sector. This study extends agency theory beyond shareholder primacy and examines how firms navigate sustainability shifts under changing stakeholder power.Design/methodology/approach: A qualitative single-case study was conducted on PALMO (a pseudonym), an Indonesian palm oil company with vertical integration. The company’s trajectory from 1993 to 2023 was traced through interviews, focus group discussions, document reviews, and site visits. The analysis draws on the Sustainability Phase Model, extended agency theory, and the four pillars of corporate governance (ethical behavior, transparency, accountability, and sustainability).Findings/Results:  PALMO’s sustainability trajectory was uneven. Progress accelerated when external pressure intensified or when internal coordination was effective, and slowed during periods of weak oversight or shifting priorities. Changes in the influence of principals (buyers, NGOs, regulators, and shareholders) either enabled movement across sustainability phases or created new constraints on the movement. Over time, governance has expanded from basic compliance to more adaptive practices, including cross-divisional sustainability teams, sustainability-linked loans, and ESG-based performance targets. These mechanisms provide ways to manage short-term business needs alongside longer-term sustainability goals.Conclusion: Multi-principal dynamics shape both progress and setbacks in sustainability phases and inform the evolution of governance. Effective governance requires adaptive arrangements that integrate sustainability into incentives, targets, and coordination structures while maintaining strategic alignment amid ongoing tensions.Originality/value: This study extends agency theory by framing governance as a negotiation among multiple principals rather than a simple alignment with shareholders. It also enriches the Sustainability Phase Model by showing that sustainability transformations can overlap, stall, or reverse, offering theoretical and practical insights into strengthening sustainability governance in emerging market agribusiness. Keywords:  corporate sustainability, extended agency theory, corporate governance, palm oil industry, sustainability transformation